Landslide mapping with the GIS - Ribičič, Mihael (Geologija, 2003)
Any new technology allows an improved approach to the processing of expert data. The article describes how to make the recording of the data of engineering geological landslide mapping of the best possible quality by exploiting the possibilities offered by GIS. Ali input landslide data acquired during mapping, called landslide elements, were classified, as customary in GIS, into three groups: point, line and polygon elements. A list of the typical landslide elements noted in landslide survey was made for each group. Each element came with a description of its origin and appearance, the surveying method and the graphical representation in GIS. Additionally, a presentation of the landslide in three layers was introduced, historically reviewing the landslide. The first layer represented the past shapes before sliding, the second layer represented the recent signs of sliding and the third one (for old landslides) represented the shapes that arise after sliding. The graphical landslide data were connected with the attributes kept in the descriptive landslide database. The described approach involving the use of GIS considerably improves the quality of data capture in engineering geological landslide mapping. An example of a landslide map prepared according to the described system is attached to the article.